ESA Trainees Committee: Comissão de Internos da European Society of Anaesthesiology - Norte, Gustavo; Matias, Bernardo; Fernandes, Diogo Sobreira (Journal of the Portuguese Society of Anesthesiology, 2018)
ESA Trainees Committee: Comissão de Internos da European Society of Anaesthesiology